Glycosylphosphatidylinositol-Anchor Synthesis in Plants: A Glycobiology Perspective - Beihammer, Gernot; Maresch, Daniel; Altmann, Friedrich; Strasser, Richard (Frontiers in Plant Science, 2020)
More than 200 diverse secretory proteins from Arabidopsis thaliana carry a glycosylphosphatidylinositol (GPI) lipid anchor covalently attached to their carboxyl-terminus. The GPI-anchor contains a lipid-linked glycan backbone that is preassembled in the endoplasmic reticulum (ER) of plants and subsequently transferred to distinct proteins which provides them with specific features. The GPI-anchored proteins exit the ER and are transported through the Golgi apparatus to the plasma membrane. In the Golgi, the glycan moiety can be further modified by the specific attachment of sugar residues. While these biosynthetic steps are already quite well understood in mammals and yeast, comparatively little is known in plants. In this perspective we discuss the current knowledge about the biosynthesis of the GPI-anchor glycan moiety in the light of recent findings for mammalian GPI-anchor glycan modifications.